Changes in Corruption Eradication Commission In Legal Sociology Perspective - Joko Sriwidodo (Corruptio, 2020)
The Corruption Eradication Commission is an independent state institution whose job it is to carry out the duties and powers of corruption eradication free from any power. The Corruption Eradication Commission was born during the reign of President Megawati, namely through Law No. 30 of 2002 concerning the Corruption Eradication Commission. In 2019 there was a revision of the Corruption Eradication Commission Law, but the revision was opposed by the public, because the change was seen as likely to weaken the Corruption Eradication Commission. Observing the brief description above, the researcher in this paper wants to raise at least 2 problems, namely; 1), Are the three foundations for the formation and amendment of the Prevailing Laws, namely juridical, philosophical and sociological elements that have been fulfilled in the amendment of the Corruption Eradication Commission Law? 2), is the amendment to the Corruption Eradication Commission Law in accordance with the expectations and realities in society from the perspective of legal sociology? This paper would like to try to provide an overview of the Corruption Eradication Commision and the Amendment to the Corruption Eradication Commision Law, both in the prevailing legal normative theory and in current practice. This research is a normative legal research which is carried out through library research. The discussion in the research, if viewed from the aspect of fulfilling the foundation for the formation and changes of laws and regulations, then the amendments to the Corruption Eradication Commision have fulfilled these aspects, namely philosophical, sociological and juridical aspects in which the Corruption Eradication Commision itself has existed for 17 years in carry out its duties and authorities as an agency to eradicate corruption. Meanwhile, from the perspective of legal sociology, the public does not want any changes to the Corruption Eradication Commision, in which the Corruption Eradication Commision is still the institution of public trust in eradicating corruption in Indonesia.